Effectiveness of Blended Learning Modules as Correlates of Self-Efficacy of ALS Students: Basis for an Action Plan - Anduyan, Dennis B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study determined the effectiveness of blended learning modules as correlates to students' self-efficacy among students in the Alternative Learning Systems in Tagum, Davao del Norte during the second quarter of 2021. Findings will serve as bases for a proposed action plan. The researcher utilized quantitative, descriptive-correlational and predictive designs among 211 students in the Alternative Learning System in different centers in the Central Cluster in Tagum, Davao del Norte selected through random sampling. The researcher used adapted-and-modified questionnaires from the following: "Evaluating the Quality, Usability, and Potential Effectiveness of Online Learning Modules: A Case Study of Teaching with Technology Grant Recipients at the University of Tennessee, Knoxville" from Goode (2003) and “Self-Efficacy as an Engaged Learner” from Schunk and Mullen (2017). The researcher utilized mean and standard deviation, Pearson-r, and linear regression for data treatment. The effectiveness of blended learning module is high. Moreover, the student’s self-efficacy is also high. Both are manifested most of the time. There is a significant relationship between effectiveness of blended learning and student’s self-efficacy. Student’s self-efficacy is influenced on the following domains of effectiveness of blended learning modules: quality of content, usability, and potential tool for effective learning. The researcher recommends seminar and training for teachers particularly on creating and enhancing contents in the blended learning modality to improve the student’s self-efficacy.